Government of India Studies in Cooperative Farming - Planning Commission (Planning Commission, 1956)
In the beginning the farm had only an area of 101.93 acres in 80 plots. The present number of plots is 167 covering an area of 209.60 acres. All this land is in a permanently settled area and the 10-members of the farm own permanent tenancy rights, in it. 70 acres of this farm are irrigated, for paddy cultivation only from a seasonal river. The river is blocked and the water inundates this acreage. Recently a tubewell has also been sunk in the village under the Sugarcane Development Scheme. 20 acres of the farm are deriving benefit from this source of irrigation. The land is comprised in 20 different blocks of various sizes. Chauriharwa is a village of approximately 700 acres bf land. The total population of the village is 200. The main castes living in the village are the scheduled ones viz. Chamber, Mushahar and Bhar. Next to them there are the tribal people known as Dhangur. There are a few Brahmins, Rajputs and Kayasthas also who have latterly acquired farming interest in this village. The 10 members of the farm are migrants from distant villages. The people who actually work on the land are the scheduled castes and Changer and Tharu tribes. All other castes are simply owner cultivators. The economic condition of the labouring classes is very poor as compared to the owning classes. The average size of holding in the village is only about 2 to 2½ acres.
Studies in Cooperative Farming
Government of India